The Analysis of Maqashid Syariah on the Use of Fiat Money and Dinar Dirham - Fatimah Zahara (Budapest International Research and Critics University, 2020)
Money as a medium of exchange, has at least two forms, namely fiat money and dinar dirham. This paper discusses the use of fiat money and the use of gold and silver as a currency with its advantages and disadvantages. Furthermore, this article also compares the use of fiat money and dinar dirhams as currency. This paper answers the question of whether gold and silver are the only metals accepted as the currency in the economic system, while other currencies are not. The results of this study indicate that, although the hadith is more likely to state that gold and silver as money, it is not limited to gold and silver. By law, 'Illah of thamaniyyah' which is not restricted to gold and silver but money in general, is supported by Ibn Taymiyah's opinion. In addition to that, the principle of ibahah where in muamalah everything is allowed, as long as it is not prohibited by the texts (Al-Quran and Sunnah). Maqashid Al-Shariah allows other forms other than gold and silver to be used as currency, if the conditions are demanding so. Metals other than gold and silver are accepted, as long as it can facilitate sharia activities such as paying zakat and rejecting usury.